Building High‐Rate Nickel‐Rich Cathodes by Self‐Organization of Structurally Stable Macrovoid. Issue 7 (11th February 2020) - Kalluri, Sujith; Cha, Hyungyeon; Kim, Junhyeok; Lee, Hyomyung; Jang, Haeseong; Cho, Jaephil
Abstract: Nickel‐rich materials, as a front‐running cathode for lithium‐ion batteries suffer from inherent degradation issues such as inter/intragranular cracks and phase transition under the high‐current density condition. Although vigorous efforts have mitigated these current issues, the practical applications are not successfully achieved due to the material instability and complex synthesis process. Herein, a structurally stable, macrovoid‐containing, nickel‐rich material is developed using an affordable, scalable, and one‐pot coprecipitation method without using surfactants/etching agents/complex‐ion forming agents. The strategically developed macrovoid‐induced cathode via a self‐organization process exhibits excellent full‐cell rate capability, cycle life at discharge rate of 5 C, and structural stability even at the industrial electrode conditions, owing to the fast Li‐ion diffusion, the internal macrovoid acting as "buffer zones" for stress relief, and highly stable nanostructure around the void during cycling. This strategy for nickel‐rich cathodes can be viable for industries in the preparation of high‐performance lithium‐ion cells. Abstract : A nickel‐rich cathode with a nanoparticle‐buffer layer induced macrovoid is developed via a one‐pot coprecipitation method without using surfactants/etching agents. The initial nanosized primary particles are dispersed toward the surface during the calcination process, which induces the nanoparticle‐based buffer zone and the structural stability. The prepared cathode material demonstrates a high specific capacity with strong structural integrity under the high C‐rate.